The Legal Basis for Intellectual Property Protection: A Focus on Trademarks - Dzikir, Naufal (Verdict: Journal of Law Science, 2024)
Legal protection of intellectual property, especially brands, is very important in today’s era of globalization and digital economy. A brand is not only a trade identity but also a part of an intangible asset that has high strategic value. This study aims to analyze the legal basis of intellectual property protection, especially trademarks, from a normative juridical perspective, as well as assess the effectiveness of legal implementation through case studies of trademark infringement in Indonesia. This research uses a normative juridical approach method by examining national and international laws and regulations, as well as literature studies from Scopus-indexed legal journals. The secondary data used were analyzed descriptive-qualitatively to find gaps and implementable constraints in brand protection. The results of the study show that Indonesia already has a sufficiently adequate legal apparatus, namely Law Number 20 of 2016 concerning Trademarks and Geographical Indications which is in line with international provisions such as the TRIPS Agreement and the Paris Convention. However, the effectiveness of the implementation of this regulation is still constrained by weak law enforcement, lack of public understanding, and challenges from digital-based brand infringement. The implications of this research lead to the need to strengthen legal institutions, public education, and technology-based policy innovations for more effective brand protection. Therefore, a more proactive and collaborative regulatory approach between governments, business actors, and the public is needed to realize a resilient and globally competitive brand protection system.